Psychosocial functioning in adolescents with non-suicidal self-injury: the roles of childhood maltreatment, borderline personality disorder and depression - Ghinea, Denisa; Fuchs, Anna; Parzer, Peter; Koenig, Julian; Resch, Franz; Kaess, Michael (Borderline Personality Disorder and Emotion Dysregulation, 2021)
There is a lack of studies examining psychosocial functioning in patients with non-suicidal self-injury (NSSI), especially in adolescents, and rates of impaired functioning in existing literature vary considerably. These variations may be attributable to further risk factors that influence psychosocial functioning. Thus, the aim of the study was to examine whether adolescent NSSI patients with childhood maltreatment (CM), a known risk factor for lower psychosocial functioning, may differ from adolescent NSSI patients without CM, and whether these differences may be explained by the severity of comorbid disorders. Specifically, we examined whether severity of borderline personality disorder (BPD), depression and posttraumatic stress disorder may explain differences in psychosocial functioning in NSSI patients with and without CM.